Baseline characterization of the practices and use of local feed ingredients among processors in Zambia - Manyise, Timothy; Kasanga, Gregory; Ahmad Fatan, Nurulhuda; Yossa, Rodrigue; Rossignoli, Cristiano (2024)
This dataset presents baseline survey data from 187 feed ingredient processors across Zambia’s Luapula, Lusaka, Eastern, and Northern provinces, gathered as part of the FASA project to advance sustainable aquaculture practices. The data provide foundational insights into the role of local feed ingredients in supporting sustainable fish farming, offering a detailed overview of feed processors' characteristics and local ingredient sourcing and use. Additionally, it assesses processors’ knowledge of local ingredient inclusion in fish feed, identifying areas for capacity building. The dataset documents current practices and innovations in feed production, as well as challenges and barriers faced by stakeholders in using local ingredients, presenting a comprehensive view of sector limitations. This baseline data serves as a resource for policymakers, researchers, and practitioners, providing an evidence-based foundation to inform targeted interventions, foster sector growth, and improve productivity, resilience, and economic outcomes in Zambia’s aquatic feed sector.